2020
DOI: 10.1111/1744-9987.13594
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the outcomes in ulcerative colitis patients undergoing granulocyte and monocyte adsorptive apheresis as remission induction therapy: A multicenter cohort study

Abstract: Ulcerative colitis (UC) patients harbor activated myeloid leukocytes, which exacerbate and perpetuate UC by releasing inflammatory cytokines. Granulocyte and monocyte adsorptive apheresis (GMA) with an Adacolumn depletes elevated myeloid leukocytes, inducing efficacy with favorable safety. To understand how the clinical outcome with GMA is affected by prior corticosteroid treatment or concomitant immunomodulators, a retrospective multicenter study in 102 UC patients, who had not responded well to first‐line me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The mechanism underlying GMA involves the Adacolumn, which is filled with cellulose acetate (CA) beads, interacting with fragment crystallizable‐gamma receptor (FcγR) expressed at the surface of activated leukocytes and selectively adsorbing granulocytes and monocytes from the systemic circulation 2 . Numerous reports have described the clinical efficacy and safety of GMA in patients with active UC 3‐22 . Previous reports have demonstrated that patients who were most likely to respond to GMA tended to be first attack cases and were steroid‐naïve with short disease duration and low disease activity 9‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying GMA involves the Adacolumn, which is filled with cellulose acetate (CA) beads, interacting with fragment crystallizable‐gamma receptor (FcγR) expressed at the surface of activated leukocytes and selectively adsorbing granulocytes and monocytes from the systemic circulation 2 . Numerous reports have described the clinical efficacy and safety of GMA in patients with active UC 3‐22 . Previous reports have demonstrated that patients who were most likely to respond to GMA tended to be first attack cases and were steroid‐naïve with short disease duration and low disease activity 9‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…There were eight studies that evaluated the efficacy of CAP in patients having UC with insufficient response to thiopurines (Table 1 )[ 36 , 37 , 42 , 58 - 62 ]. These studies include three prospective studies, two retrospective studies, one historical cohort study, one single-arm, open-label, multicentre trial, and one multicenter cohort study.…”
Section: Efficacy Of Cap In Patients With Uc Showing Insufficient Res...mentioning
confidence: 99%
“…Regarding the rate of steroid-free remission, two studies[ 59 , 62 ] compared the rates of steroid-free remission between the patients concomitantly treated with thiopurines or IM and the patients treated without them. These studies showed that significant differences were not observed between the patients concomitantly treated with thiopurines or IM and patients treated without them.…”
Section: Efficacy Of Cap In Patients With Uc Showing Insufficient Res...mentioning
confidence: 99%
See 2 more Smart Citations